2023
DOI: 10.3390/agronomy13082128
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Trait Association Analysis of 27 Pearl Millet Landraces in Southern Tunisia

Abstract: Pearl millet (Pennisetum glaucum (L.) R. Br., 2n = 2x = 14, Poaceae), is a cross-pollinated, warm-season crop grown worldwide. To select genotypes for breeding pearl millet cultivars that adapt to drought condition in southern Tunisia, we evaluated the grain yield (GY) and yield-related traits using a set of 27 landraces at two locations in southern Tunisia for two grown seasons (2019 and 2020). The genetic variability, phenotypic and genotypic association, and path coefficient (PC), based on grain yield (GY) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
0
0
0
Order By: Relevance
“…In this study, the accuracy values of the majority of variables, especially AUDPC and IT, were very high, as were the accuracy values of the rest of the variables; in general, estimates above 0.70 are sufficient to explicitly conclude the genetic value of genotypes [31,32]. In addition, AUDPC showed the highest selection genetic gain percent (−61.13%), and in general, the MGIDI provided a total SD of −59.12% for traits with decreased sense.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…In this study, the accuracy values of the majority of variables, especially AUDPC and IT, were very high, as were the accuracy values of the rest of the variables; in general, estimates above 0.70 are sufficient to explicitly conclude the genetic value of genotypes [31,32]. In addition, AUDPC showed the highest selection genetic gain percent (−61.13%), and in general, the MGIDI provided a total SD of −59.12% for traits with decreased sense.…”
Section: Discussionmentioning
confidence: 56%
“…According to the results, we found that the selection based on MGIDI provided satisfactory gain. The measured MGIDI, based on the BLUP data from multiple traits in two years, selected 20 resistant genotypes (17,80,111,127,81,38,37,61,132,59,Dorfak,58,46,141,18A,54,27,140,51,and 32) that highly overlapped with selected genotypes using cluster analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations